Nalar Sufistik dan Satire Nashruddin Hodja dalam Sastra Hikayat Jenaka - Wildani Hefni; Ayis Mukholik (Islamika Inside: Jurnal Keislaman dan Humaniora, 2021)
Abstract: This article explores the Sufistic thoughts of Nashruddin Hodja with a focus on the study of the moral and spiritual messages analyze which contained in the works of comical tales. One of humorous Sufis who implemented his Sufism work is Nashruddin Hodja. He used this approach to educate the public and criticize the unjust rulers at the time of the 13th-century Mongol invasion of Turkey. The primary source of this research is a book written by Hodja under the title The Turkish Jester or The Pleasantries of Cogia Nasr Eddin Effendi: 1984. The researchers used qualitative methods analyzed using Schleiermacher's hermeneutic approach, which is grammatical interpretation and psychological interpretation. The result of this research indicates Nashruddin Hodja has Sunni Sufistic thought in terms of text and his psychology. The topics raised are human attitudes to God, individual and social ethics. Then the result can be formulated as a new approach in Sufism likes purifying the soul and fostering morals with an esoteric humorous nuance.